Working together: reflections on how to make public involvement in research work - Lynn McVey; Tina Frost; Basma Issa; Eva Davison; Jamil Abdulkader; Rebecca Randell; Natasha Alvarado; Hadar Zaman; Nicholas Hardiker; V.-Lin Cheong; David Woodcock (Research Involvement and Engagement, 2023)
Plain English summary Involving members of the public in all stages of research as equal partners is a powerful way to make research more relevant. This paper shares an example of such involvement, from a study about falls prevention in English hospitals. Developed by a team of lay people and professional researchers, the paper looks at how we worked together, drawing on evaluations we carried out about how the study took patient and public perspectives into account, and on personal reflections we wrote. Public involvement had a positive effect on the project and the individuals involved, but there were also difficulties. Positive impacts included lay people ensuring the study focused on what mattered most to patients and their families and feeling they had done right by their personal experience of the study’s subject. Negative impacts included the potential for people to feel overwhelmed by the changes in organisations or in wider society needed to address the issues being explored by a research study, which could cause them to question why they became involved in the first place. The paper ends with practical recommendations about working together, covering things such as helping lay people with the emotional impact of involvement from the beginning to the end of projects; finding ways to ensure everybody is treated in the same way and solving practical problems; and tips on leading and supporting groups of this kind, especially with personal issues like trusting each other.